Temporal Evolution of Substorm‐Driven Global Alfvén Wave Power Above the Auroral Acceleration Region. Issue 4 (18th April 2020) - Keiling, Andreas; Thaller, Scott; Dombeck, John; Wygant, John
Abstract: The onset of substorms is associated with bursty enhancements of Alfvén wave power throughout the magnetotail. While impossible to assess the total Alfvén wave power in the entire magnetotail, we have instead monitored waves that are funneled into the auroral acceleration region, in order to assess the temporal evolution of Alfvén wave power above the nightside auroral zone in relation to substorm phases. The substorms were grouped by three conditions: nonstorm periods, storm periods, and all (unconditioned) periods. Using superposed epoch analysis, we found that the global magnetohydrodynamic Alfvén wave power increased significantly at onset for all three conditions, while a power decrease to preonset values occurred within 2 hr. Specifically, the peak inflowing power during the expansion phase was 5.7 GW for unconditioned substorms, 5.6 GW for nonstorm‐time substorms, and 7.8 GW for storm‐time substorms. These results correspond to power increases with respect to preonset values of 138%, 366%, and 200%, respectively. Additional analysis in relation to the aurora was performed for nonstorm‐time substorms only. During the expansion phase, about 50% of the Alfvén wave power over the entire nightside auroral zone is collocated with the auroral bulge region. Furthermore, the total inflowing Alfvén wave power over the entire nightside auroral zone is 17% of the conjugate auroral power, while the inflowing power over the auroral bulge region is 32% of the conjugate aurora. However, allowing for a finite absorption efficiency inside the auroral acceleration region, the likely average Alfvénic contributions to the aurora are approximately 10% and 18%, respectively. Key Points: We calculated the rise and fall of global Alfvén wave power above the AAR throughout the substorm cycle Alfvén wave power significantly increases after onset over the entire nightside auroral zone and especially over the auroral bulge Alfvén wave power can account for low‐altitude Alfvénic electron power and for significant fraction of aurora during the expansion phase